1995
DOI: 10.1038/jcbfm.1995.107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soluble Complement Receptor-1 on Neutrophil Accumulation after Traumatic Brain Injury in Rats

Abstract: Summary: As part of the acute inflammatory response, neutrophils accumulate in the central nervous system af ter injury. Recently, a soluble human recombinant com plement receptor (sCR1; BRL 55730; T Cell Sciences, Inc., Cambridge, MA, U.S.A.) has been developed that inhibits the activation of both the classical and the alter native pathways of complement. sCR 1 attenuates the ef· fects of the aCUte inl1ammatory response in several mod els of injury outside the central nervous system. The role of complement in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(61 citation statements)
references
References 20 publications
1
57
0
1
Order By: Relevance
“…In addition, posttraumatic brain neutrophil accumulation, known to be C3-dependent (Kaczorowski et al, 1995;You et al, 2007), was similar in MBL KO and WT mice. Thus, MBL A/C, and hence the lectin pathway, appears to be dispensable for terminal complement activation after CCI, in agreement with previous reports from our group and others that indicate a predominant role for the alternative pathway in TBI (Rancan et al, 2003;You et al, 2007).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In addition, posttraumatic brain neutrophil accumulation, known to be C3-dependent (Kaczorowski et al, 1995;You et al, 2007), was similar in MBL KO and WT mice. Thus, MBL A/C, and hence the lectin pathway, appears to be dispensable for terminal complement activation after CCI, in agreement with previous reports from our group and others that indicate a predominant role for the alternative pathway in TBI (Rancan et al, 2003;You et al, 2007).…”
Section: Discussionmentioning
confidence: 78%
“…Activation of complement plays a role in posttraumatic brain inflammation. Intracerebral complement activation occurs in traumatic human brain (Bellander et al, 2001;Schmidt et al, 2005;Stahel et al, 1998), and genetic or pharmacological inhibition of terminal complement components reduce brain neutrophil accumulation, blood-brain barrier damage, apoptosis, and neurologic dysfunction in experimental TBI models (Kaczorowski et al, 1995;Leinhase et al, 2006;Rancan et al, 2003). Complement activation may be mediated by three distinct pathways: The classical pathway (initiated by antigen-antibody aggregates and proceeding through C1q, C4, and C2), the alternative pathway (initiated by C3b and proceeding through factor B and factor D), and the lectin pathway (initiated by mannose binding lectin (MBL) and proceeding through C4 and C2).…”
Section: Introductionmentioning
confidence: 99%
“…posttraumatic brain neutrophil accumulation was not decreased in C4 À/À mice compared with WT. We and others found that brain neutrophil accumulation after cerebral contusion in rodents is C3-dependent, as shown in rats using a pharmacologic C3 convertase inhibitor (Kaczorowski et al, 1995) and in mice deficient in C3 in this study. Collectively, these findings imply that C3-independent mechanism(s) mediate the biologic effects of C4 in our CCI model.…”
Section: Discussionmentioning
confidence: 82%
“…The investigators showed beneficial effects on histopathologic or functional outcome of pharmacologic C3 convertase inhibitors (Kaczorowski et al, 1995;Leinhase et al, 2006b), genetic inhibition of factor B (a component of the alternative pathway) (Leinhase et al, 2006a), or of astrocyte-specific overexpression of an endogenous C3 convertase inhibitor (Rancan et al, 2003). These studies suggested that terminal complement activation may induce secondary injury after TBI; however, the pathway(s) that initiate complement activation after TBI have not been completely defined (Leinhase et al, 2006a).…”
mentioning
confidence: 99%
“…In a study of traumatic brain injury model in rat, recombinant sCR1 reduced tissue neutrophil infiltration and relieved local immune inflammation by inhibiting activation of the complement system. 17 Dobschuetz et al 18 have shown that sCR1 effectively improved the pancreatic ischemia-reperfusion-induced microcirculation in rats and they also described the possibility of treatment after post-ischemic pancreatitis. Li et al 19 showed that recombinant sCR1 effectively inhibited complement activation during cardiopulmonary bypass in humans, and referred the tolerance and improvement of vascular functions in infant's case.…”
Section: Discussionmentioning
confidence: 99%